Gaya Kepemimpinan Kepala Madrasah dalam Mengembangkan Mutu Tenaga Kependidikan - Vastha Vusvitha; Zainal Berlian; Dewi Warna (Studia Manageria, 2020)
This study aims to describe and analyze the principal's leadership style as well as supporting and inhibiting factors in developing the quality of the teaching staff at Madrasah Aliyah Miftahul Ulum Tanjungpinang, Riau Islands. This research uses a descriptive qualitative approach with a case study research design. Data collection techniques used were observation, interviews and documentation. Techniques in the validity of data use persistence and triangulation observations. The results of the study can be explained as follows: (1) the leadership style of Miftahul Ulum Miftahul Ulum Tanjungpinang Madrasah that is responsible, energetic and high spirits, motivating, disciplined, and innovating, (2) the leadership style of the Miftahul Ulum Miftahul Ulum Madrasah leadership in Tanjungpinang is democratic, seen from the way madrasah head who respects the potential and intelligence of his subordinates, gives his subordinates the opportunity to be fully involved in madrasah development, freedom of opinion, decisions made based on mutual agreement, and (3) supporting factors for quality development of education staff who seek to optimize services for Madrasah Aliyah Miftahul Ulum Tanjungpinang. Then the ability to communicate well cares for all committed members and discipline. While the inhibiting factor is the existence of schools in the middle of the city that compete with other leading schools.